(untitled) (Bioscience Journal, 2019)
This study evaluated the total polyphenols content and the antioxidant activity of the infusion prepared with leaves from Achillea millefolium L. plants treated with salicylic acid (SA). Field cultivated plants received SA foliar applications (T1: control; T2: 1.0 mmol L-1 applications at 20, 60 and 100 days after planting - DAP and T3: 1.0 mmol L-1 applications at 100 DAP during three days). The infusions from SA treated plants showed higher levels of total polyphenols and flavonoids compared to the control one. T2 and T3 infusions showed increases in the antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH), nitric oxide (NO) and ferric-reducing antioxidant power (FRAP) tests. However, only T2 treated plants had higher antioxidant activity by inhibition of lipid peroxidation (TBARS). It was concluded that elicitation of A. millefolium plants with SA can be considered an adequate strategy to increase the production of bioactive compounds and the antioxidant capacity of infusions.